Sustained capillary enlargement induced by angiogenic gene therapy does not support post-ischemic muscle recovery of hyperlipidemic mice - Wirth, Galina; Juusola, Greta; Laakso, Hanne; Laham-Karam, Nihay; Ylä-Herttuala, Seppo; Korpisalo, Petra (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundHyperlipidemia is known to impair endothelial function. We have recently shown that hyperlipidemia also blunts native post-ischemic capillary enlargement that is important for efficient skeletal muscle recovery from ischemia as it supports the recovery of arterial driving pressure and through intussusception increases capillary density. The correction of capillary reactivity under hyperlipidemia could, therefore, improve post-ischemic skeletal muscle recovery. This study tested the ability of adenoviral (Ad) vascular endothelial growth factor (VEGF) gene therapy to rescue capillary enlargement and improve post-ischemic muscle repair in hyperlipidemic mice.MethodsAdVEGF or AdLacZ-control vector were delivered into the calf muscles of aged, hyperlipidemic LDLR−/−ApoB100/100 mice (n = 58) after induction of acute ischemia. The effects of AdVEGF on capillary phenotype, tissue edema, restoration of blood flow parameters, microvascular hemoglobin oxygenation and tissue damage/regeneration were evaluated using immunohistological analyses, magnetic resonance imaging, contrast-enhanced ultrasound imaging, photoacoustic imaging and histological analyses, respectively, up to 29 days after induced ischemia and gene transfer.ResultsIt was found that AdVEGF gene therapy was able to promote capillary enlargement (P < 0.05) that led to recovery of arterial driving pressure in ischemic LDLR−/−ApoB100/100 muscles. However, capillary enlargement induced by AdVEGF in the hyperlipidemic mice was delayed, had a long-lasting effect (P < 0.05) and did not promote intussusception. Instead, side-effects of VEGF-induced capillary enlargement, i.e., tissue edema (P < 0.01) and subsequently delayed blood flow recovery (P < 0.05), aggravated ischemic tissue damage (P < 0.01).ConclusionHyperlipidemia or old age did not seem to impair AdVEGF-induced capillary enlargement. However, regarding the side-effects of capillary enlargement, therapies trying to promote post-ischemic skeletal muscle recovery through angiogenesis should consider not only capillary size or density but also timing and dynamics of the capillary changes.